Identification of mouse cochlear progenitors that develop hair and supporting cells in the organ of Corti - Jinshu Xu (Nature Portfolio, 2017)
The adult mammalian cochlear sensory epithelium consists of mechanosensory hair cells and supporting cells but hair cells cannot regenerate. Here, the authors identify multipotent progenitors that arise fromEya1-expressing otic cells that can regenerate hair cells in mice after 1 week of age.